Detection of atovaquone-proguanil resistance conferring mutations in Plasmodium falciparum cytochrome b gene in Luanda, Angola - Pimentel, Sónia (2006)
Background: The fixed dose combination atovaquone-proguanil is a recently introduced antimalarial for treatment and prophylaxis of Plasmodium falciparum malaria. It is highly effective with a good tolerability profile and a convenient prophylactic regimen. Nevertheless, cases of treatment failure have already been reported, which have been associated to mutations in the cytochrome b gene of the Plasmodium (pfcytb). The presence of atovaquone-proguanil in vivo resistance conferring mutations in pfcytb gene in Luanda, Angola, was investigated, in order to make recommendations on prescribing this antimalarial as prophylaxis for travellers. Methods: Two hundred and forty nine blood samples from children hospitalized at Luanda Pediatric Hospital for malaria were studied. The PCR-RFLP methodology was used in order to identify pfcytb wild type codon 268 and two point mutations: T802A and A803C. Results: All samples were identified as wild type for pfcytb gene at codon 268. In the studied population, no mutations associated to atovaquone-proguanil treatment failure were found. Prevalence of the studied mutations in the region was estimated to be less than 0.77% (99% significance level). Conclusion: Atovaquone-proguanil can be recommended for use by travellers to Luanda with expected high efficacy. This represents an improvement compared to other currently used prophylatic antimalarials in this region. However, it is imperative to continue surveillance.